2017
DOI: 10.1515/foli-2017-0009
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Global Financial Market Recovery after the 2008 Global Financial Crisis

Abstract: The Financial Crisis of 2007-2009 plunged countries into a Great Recession and focused the world’s attention on the global stock markets. The global contagion has a major impact on global stock markets, with the U.S. DJIA falling to 6,547.05 on March 9, 2009 from a high of 14,164.53 on October 9, 2007, with a loss of more than 54%. Other stock markets also had a precipitous drop during the financial crisis. However, some equity markets have recovered while others have not. This paper looks at how global market… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The highest permanent contraction in GDP growth level comes from combined banking and currency or political crises, while the effects are generally worse for the less developed economy. In addition, Foo and Witkowska [92], researching the post-crisis recovery of global securities markets, found that in less developed countries, the recovery of securities markets occurred with a higher level of volatility. Similarly, Barnichon et al [93], by comparing the results of econometric modelling of the growth of the US economy, concluded that it is impossible to return to the pre-crisis trajectory of GDP.…”
Section: Financial Depth-economic Growth Nexus During Gfcmentioning
confidence: 99%
“…The highest permanent contraction in GDP growth level comes from combined banking and currency or political crises, while the effects are generally worse for the less developed economy. In addition, Foo and Witkowska [92], researching the post-crisis recovery of global securities markets, found that in less developed countries, the recovery of securities markets occurred with a higher level of volatility. Similarly, Barnichon et al [93], by comparing the results of econometric modelling of the growth of the US economy, concluded that it is impossible to return to the pre-crisis trajectory of GDP.…”
Section: Financial Depth-economic Growth Nexus During Gfcmentioning
confidence: 99%
“…The impact of crises on individual economies tends to vary across countries and is visible both in its first phase, i.e. during the emergence of its negative effects, and in the post-crisis economic growth (Foo & Witkowska, 2017). Crises have been analysed and researched by many scientists worldwide (Clemente-Suárez et al, 2021;Sombultawee et al, 2022).…”
Section: Introductionmentioning
confidence: 99%